PENGARUH PENCEMARAN UDARA TERHADAP TERJADINYA AIR BORNE DISEASE DAN GANGGUAN KESEHATAN LAINNYA - Naris Dyah Prasetyawati; Sigid Sudaryanto (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2021)
Environmental quality deterioration occurs globally, both in developed and developing countries. The concentration of greenhouse gases in the atmosphere has increased, with the occurrence of the process of climate change (climate change) and global warming, which impacts and effects can be felt in everyday life. The development development in various cities and regions still ignores sustainable development or sustainable development. The growth of an area vertically or horizontally has an impact on the occurrence of pollution to water, soil and air. Although naturally air can carry out self-purification, according to WHO, the current condition has reached an alarming stage, this is because nine out of 10 people in the world breathe polluted air in turn. Meanwhile, more than half of the world's population currently live in urban environments. This article is written to explore the extent of the impact of air pollution that is currently occurring with the incidence of air borne disease on a local, regional and global scale. The current decline in air quality is more predominantly caused by human activities in the form of transportation and increased industrial activities. Poor air quality is associated with an increase in the prevalence of clinical manifestations of asthma and allergies, especially in children, this is because the development of the respiratory organs in children has not yet been formed and is accustomed to breathing in excess amounts of air pollutants. He further stated that air pollution kills around seven million people every year. Efforts to monitor air environment conditions are a good step to provide an early warning system of actions that must be taken so as not to cause greater impacts and losses.